Stages of a Transtheoretical Model as Predictors of the Decline in Estimated Glomerular Filtration Rate: A Retrospective Cohort Study - Daisuke Takada; Susumu Kunisawa; Akira Kikuno; Tomoko Iritani; Yuichi Imanaka (Journal of Epidemiology, 2022)
Background: The transtheoretical model (TTM) is composed of the multiple stages according to patient’s consciousness and is believed to lead people to realize the importance of healthier behaviors. We examined the association of TTM stages with the decline of estimated glomerular filtration rate (eGFR). Methods: We used the annual health checkup data and health insurance claims data of the Japan Health Insurance Association in Kyoto Prefecture between April 2012 and March 2016. TTM stages of change obtained from questionnaires at the first health checkup and categorized into six groups. The primary outcome was defined as a more than 30% decline in eGFR from the first health checkup. We fitted multivariable Cox proportional-hazards model for time-to-event analyses adjusting for age, sex, eGFR, body mass index, blood pressure, blood sugar, dyslipidemia, uric acid, urinary protein, and existence of kidney diseases at first health checkup. Results: We analyzed 239,755 employees and the mean follow-up was 2.9 (standard deviation, 1.2) years. As compared with the stage 1 group, the risk of eGFR decline was significantly low in the stage 3 group (hazard ratio [HR] 0.77; 95% confidence interval [CI], 0.65–0.91); stage 4 group (HR 0.80; 95% CI, 0.65–0.98); and stage 5 group (HR 0.79; 95% CI, 0.66–0.95). Conclusion: Compared with the precontemplation stage (stage 1), the preparation, action and maintenance stages (stages 3, 4, and 5), were associated with a lower risk of eGFR decline.